P245 The Relationship Between the Endoscopic Healing Index and Magnetic Resonance Enterography In Crohn's Disease Patients. (30th January 2023) - Smith, E; Chen, J; Pan, Y; Mahtani, P; Lukin, D; Ahmed, W; Longman, R; Burakoff, R; Scherl, E; Battat, R
Abstract: Background: The endoscopic healing index (EHI) is a serum biomarker panel that identifies endoscopic Crohn's Disease (CD) activity. Endoscopy and biomarkers are limited in assessing small bowel disease compared to magnetic resonance enterography (MRE). The Simplified Magnetic Resonance Index of Activity (MaRIAs) is validated to detect CD activity. Data are lacking on the relationship between EHI with other endpoints. This study performed the first assessment of EHI to diagnose CD-related intestinal inflammation on MRE using the MaRIAs score. Methods: Data were extracted on CD patients with EHI within 90 days of MRE. We assessed the diagnostic accuracy of EHI for any (MaRIAs≥1) or severe (MaRIAs≥2) MR inflammation identified on MRE using area under the receiver operator characteristic (AUROC) curve analyses. Proportions with inflammation on MRE were compared between groups above and below the identified EHI and FCAL threshold. Analyses were repeated between EHI and active endoscopy (SES-CD≥5), fecal calprotectin (FCAL>50, >250), and clinical symptoms (CD PRO-2≥8). Results: 241 MREs uniquely paired to either EHI or FCAL from 155 patients, mean age was 42 years, 50.3% were female, 83.2% of patients had small bowel involvement, and 29.7% had penetrating disease. The mean time between EHI to MRE was 28 days, and the mean time between FCAL and MRE was 24 days. Both EHI and FCAL had similar accuracy to diagnose inflammation (AUROC: EHI:0.635-0.651, FCAL:0.680-0.708). Optimal EHI values were 42 and 26 for inflammation on MRE and endoscopy, respectively. Patients with EHI≥42 (100% vs. 63%, p=0.002), FCAL>50µg/g (87% vs. 64%, p<0.001) and FCAL>250µg/g (90% vs. 75%, p=0.02) had higher rates of MaRIAs≥1 compared to lower values. EHI differentiated ileitis more than FCAL (delta: 24-25% vs. 11-21%). Patients with low FCAL had high rates (59-69%) of active endoscopic disease, whereas those with low EHI rarely (6%) with endoscopic activity. Patients with FCAL≥50µg/g had higher rates of severe inflammation compared to FCAL<50µg/g (75% vs. 47%, p<0.001) whereas smaller differentiation existed for EHI. In patients with CD PRO-2 scores, clinical remission was not associated with disease activity corresponding to active EHI, endoscopy, or MRE. Conclusion: In CD patients predominantly with ileal involvement, EHI>42 and FCAL>50 were both specific to confirm inflammation on MRE. Lower EHI values (<42), but not low FCAL (<50), were associated with lower rates of severe radiologic inflammation. MRE inflammation was frequently present in the presence of low EHI and FCAL with similar proportions of false negative MRE results. However, the absence of endoscopic inflammation was only associated with low EHI, but not low FCAL values.